Effects of biochar obtained from grape agricultural residues on biogas generation - Diaz Vento, Ingrind (2022)
The wine industry produces a large amount of waste every year, this waste is generally not properly managed and becomes an environmental and sanitary hazard. On the other hand, the production of clean energies such as biogas from cattle manure has become an important energy resource. The aim of this study was to evaluate the biochar obtained by torrefaction of agricultural grape residues in the production and quality of biogas produced by anaerobic digestion of cattle manure. The study was carried out in the experimental area of the La Católica farm, located in Majes, Arequipa-Peru. A multiple factorial design composed of nine treatments was used to produce biochar, where the operating parameters were temperature and torrefaction time; and response parameters were grape residue mass yield, biogas yield and quality. The results indicate that temperature and torrefaction time significantly influence biochar production, with 40 min and 263.00°C being ideal values. Furthermore, biochar efficiently reduces the CO2 and H2S content up to 22% and 0.78 ppm, respectively, of the biogas. However, no impact on biogas and methane yields was observed. The use of waste to produce biochar and improve the quality of biogas can be replicated wherever the wine industry is developed, both in regions close to the coast and in mountainous regions of the Andean countries, achieving an integrated agroecological system, as it promotes sustainable agricultural practices, thus conserving biocultural resources.